Family Structure, Children, and Law - Vivian E. Hamilton (Washington University Journal of Law & Policy, 2007)
The claim that “marriage is good for children” has long helped ground arguments for the institution’s extraordinary state support. But how sound is this empirically based claim and the normative conclusion drawn from it—namely, that marriage merits this extraordinary support? This Essay reviews recent studies in the social sciences and determines that the “marriage effect” on children is difficult to isolate and all too often vastly overstated. Thus the normative conclusion, inextricably linked to its supposed empirical premise, is deeply flawed.
Keywords: Child welfare; Unmarried couples; Domestic relations law reform; Children of divorced parents; Family relations; Parent and child (Law); United States